MICROWAVE ASSISTED RAPID COMBINATORIAL SYNTHESIS OF SILVER NANOPARTICLES USING E.COLI CULTURE SUPERNATANT - ARABINDA MAHANTY; RANADHIR BOSU; PRAGNYA PANDA; SURYA PRAKASH NETAM; BIPLAB SARKAR (International Journal of Pharma and Bio Sciences, 2013)
Synthesis of nanoparticles is central to research and applications in nanotechnology. Silver nanoparticle is one of the most commercially successful nanoparticles due to their wide applicability in various areas such as electronics, catalysis, energy and medicine etc. Although,variety of physicaland chemical based synthetic methods of silver nanoparticles have been reported, these are either not cost-effective or uses chemicals, which are environmental toxicants. Though, biological synthesis of silver nanoparticles is a cost-effective and eco friendly method but also a time consuming one. The present study describes a rapid method of silver nanoparticle synthesis using E. coli culture supernatant along with microwave irradiation. This method is biological and physical based combinatorial method, capable of synthesizing silver nanoparticles of smaller size (8-9 nm) in about 10 minutes at alkaline medium in comparison to 24-36 hours and neutral medium used by conventional microbial method. This method is cost efficient, safe, consume less time and can be applied for up scaling and industrial use.